Improving Speaking Skills Using the Cooperative Method Jigsaw Technique for Third Grade Students of SD Negeri 3 Kedungbanteng Banyumas - Nia Ulfa Martha; Dyah Wijayawati (BAHASTRA, 2021)
This research has a goal that can be formulated, among others (1) describes improving speaking skills through cooperative methods of jigsaw techniques in students of grade III State Elementary School 3 Kedungbanteng Banyumas; and (2) describe changes in the behavior of students of class III Elementary School 3 Kedungbanteng Banyumas after being given learning speaking skills through cooperative methods jigsaw techniques. The method used is PTK. In the PTK method researchers help teachers overcome problems learning speaking skills in the classroom. Learning outcomes speak cycle I 45%, cycle II 55%, and cycle III 70%. The quality of speaking learning, cycle I 46%, cycle II 76%, and cycle III 87%. In accordance with the results shown, there is an increase in learning speaking skills with cooperative methods of jigsaw techniques.